É POSSÍVEL LER CRITICAMENTE O FENÔMENO ESPORTIVO NAS AULAS DE EDUCAÇAO FÍSICA NO ENSINO MÉDIO? UMA CARTA PEDAGÓGICA, UM DESABAFO - Maldonado, Daniel Teixeira (Revista Didática Sistêmica, 2026)
This pedagogical letter aims to report an experience with the thematic approach to sport in Physical Education classes at the Federal Institute of São Paulo - Jacareí campus, with the intention of problematizing the sporting phenomenon and its relationship with the social function of the curricular component in vocational education at the secondary level. The teaching activities took place between May and October 2025, with 80 students from the Administration and Computer Science courses integrated into High School. The educational experience demonstrated the power of the critical-liberating curriculum of Physical Education as an epistemological basis for teachers to problematize reality, enabling students to critically interpret the world regarding the historical, social, political, economic, and biological factors that permeate sporting practice. From this perspective, it is possible to construct new meanings and significations involving educational projects that discuss this theme in the school's daily life.